Flexural Response of Reinforced Concrete One-Way Slabs Embedded with Pet Bottles - Alhomsi, Chahed Abdulsatir (2023)
A Master of Science thesis in Civil Engineering by Chahed Abdulsatir Alhomsi entitled, “Flexural Response of Reinforced Concrete One-Way Slabs Embedded with Pet Bottles”, submitted in May 2023. Thesis advisor is Dr. Sami Tabsh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).